A lithium-sulfur battery positive electrode and preparation method thereof

By using sublimated sulfur particles and graphene composite materials with surface-loaded cerium single atoms in the positive electrode of the lithium sulfur battery, the problems of polysulfide shuttle effect and poor sulfur conductivity are solved, and the battery performance is improved, including the improvement of Coulomb efficiency, cycle stability and charge and discharge efficiency are improved.

CN119481020BActive Publication Date: 2025-03-25SICHUAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510061601.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The shuttle effect of polysulfides in lithium-sulfur batteries leads to poor electrochemical performance, and the conductivity of sulfur and discharge product Li2S, which affects the utilization rate and cycling stability of the battery.

Method used

Sublimated sulfur particles with surface-loaded cerium single atoms are used to cooperate with graphene as a positive electrode active material. Through the catalytic action of cerium single atoms and the physical barrier of graphene, the shuttle effect of polysulfide is suppressed and the conductivity of sulfur particles is improved.

Benefits of technology

Effectively inhibit the shuttle effect of polysulfides, improve the Coulomb efficiency, cycle stability and charge and discharge efficiency of the battery, and improve the utilization rate of sulfur and the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the field of lithium-sulfur secondary batteries, and relates to a lithium-sulfur battery positive electrode and a preparation method thereof, wherein the positive electrode active layer of the positive electrode comprises an active sulfur-graphene composite material, a conductive agent and polyvinylidene fluoride; the active sulfur is a sublimated sulfur particle with a surface-loaded cerium single atom. The cerium single atom catalyst in the present invention can form a strong chemical bond with polysulfide, and can effectively inhibit the polysulfide shuttle in combination with the physical barrier of graphene; cerium has a high selective adsorption to long-chain polysulfide, reduces the redox reaction energy barrier of polysulfide, improves the utilization rate of sulfur, reduces the loss of active substances, and improves the coulomb efficiency, cycle stability and charge and discharge efficiency of the battery; the conductivity of sulfur can be enhanced, and the rapid transmission of electrons in the entire electrode can be promoted, thereby improving the rate performance of the battery; at the same time, the cerium single atom can form a stable coordination structure on the sulfur surface, limit the volume expansion of sulfur during the charge and discharge process, and extend the cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium-sulfur secondary batteries, and in particular relates to a lithium-sulfur battery positive electrode and a preparation method thereof. Sublimated sulfur particles with single cerium atoms loaded on the surface and a composite of graphene are used as positive electrode active materials to effectively inhibit the shuttle effect of polysulfides, improve the conductivity of sulfur particles, and enhance the coulomb efficiency, cycle stability and charge and discharge efficiency of the battery. Background Art

[0002] With the rapid development of portable electronic devices, electric vehicles and drones, people's demand for energy storage batteries is also growing, and higher requirements are placed on the energy density and cost of energy storage batteries. Lithium-sulfur (Li-S) batteries are based on sulfur (theoretical specific capacity is 1672mAh g -1 ) is the positive electrode, lithium (theoretical specific capacity is 3840 mAh g -1 ) is the negative electrode, and the theoretical energy density is as high as 2600wh·kg -1 , is a very promising electrochemical energy storage system, with a theoretical specific energy that is five times that of currently commercialized lithium-ion batteries; at the same time, lithium-sulfur batteries have a long cycle life and can maintain a stable cycle capacity during the charge and discharge process, with a charge and discharge frequency of more than 500 times; the cost of positive electrode sulfur is low, the reserves are abundant, and it is environmentally friendly, which can reduce the cost of lithium-sulfur batteries. However, in practical applications, lithium-sulfur batteries still have some problems: (1) The poor conductivity of sulfur and the discharge product Li2S makes their utilization rate low and the battery specific capacity low. Sulfur and the discharge product Li2S are both insulating materials, which are difficult to charge and discharge when used alone. In practical applications, conductive agents need to be added to discharge sulfur; (2) During the charge and discharge process of lithium-sulfur batteries, high-order polysulfides are easily soluble in the electrolyte, migrate through the diaphragm to the negative electrode, and the back-and-forth migration causes a "shuttle effect", which seriously affects the electrochemical performance of lithium-sulfur batteries.

[0003] In order to solve the above problems and improve the electrochemical performance of lithium-sulfur batteries, researchers have conducted research in the aspects of positive electrode structure regulation, diaphragm modification, lithium negative electrode structure design, and electrolyte additives. Among them, the sulfur positive electrode material is mainly constructed by selecting a carrier to construct a sulfur composite material, among which porous carbon is a commonly used positive electrode sulfur carrier. While improving the conductivity of the sulfur positive electrode, the porous carbon material constrains sulfur and polysulfides through the physical restriction of the porous structure. In addition, polar materials (such as metal phosphides, metal sulfides, metal carbides, and metal neon oxides) have strong chemical adsorption capacity for polysulfides and are also used as positive electrode sulfur carriers to restrict polysulfides through chemical adsorption, inhibit the shuttle effect, and improve the electrochemical performance of lithium-sulfur batteries. However, the non-polar surface of porous carbon cannot effectively adsorb lithium polysulfide, resulting in rapid attenuation of battery capacity during long-term cycling. It is difficult for polar material sulfur carriers to prevent the dissolution of lithium polysulfide adsorbed on the host surface in the electrolyte. Recently, some polar materials with good conductivity (such as metals and metal compounds) have been used as catalysts for lithium-sulfur batteries. While effectively fixing lithium polysulfide, they can accelerate its conversion to solid products during the charge and discharge process, thereby greatly improving the capacity and cycle life of lithium-sulfur batteries. However, these catalysts are not reactive within the voltage range of lithium-sulfur batteries, and the use of a large amount of catalysts will lead to a loss in the overall energy density of lithium-sulfur batteries.

[0004] Single atom catalysts (SACs) can maximize the atomic utilization while minimizing the amount of catalyst used. The active components exist in the form of atoms, and each isolated single atom is considered to be a reactive center, which can provide a large number of highly dispersed active sites and greatly improve the conversion rate of reactants. In recent years, people have begun to apply SACs to lithium-sulfur batteries. For example, CN109248712A discloses a metal single atom-doped nanocarbon material catalytic carrier, which includes a nitrogen-containing carbon core-shell structure formed by a nitrogen-containing carbon shell covering a carbon core and metal single atoms distributed in the nitrogen-containing carbon core-shell structure. It has a rich porous structure and a high specific surface area, and has a strong adsorption capacity for polysulfide ions and electrochemical catalytic functions. When used as a lithium sulfide positive electrode carrier, it can enable the secondary battery to achieve rapid activation at a low cut-off voltage. CN111403702A discloses a sulfur-carrying material for a lithium-sulfur battery, which is a MXene material with a two-dimensional sheet structure, wherein the two-dimensional sheet structure has single-atom dispersed doping atoms, and the doping atoms have an electrocatalytic activity that promotes the multiphase conversion reaction of sulfur. The sulfur-carrying material can significantly improve the cycle and rate performance of the lithium-sulfur battery, and is of great significance for the further commercialization of lithium-sulfur batteries. CN113731392A discloses a single-atom electrocatalyst and a preparation method thereof, a lithium-sulfur battery positive electrode material with single-atom carbon as a polysulfide electrocatalyst, and a composite positive electrode of sulfur and catalyst is achieved by melt-filling sulfur. The carbon pore cavity skeleton structure can well accommodate high-load sulfur and physically restrict the shuttling of polysulfides. The single-atom electrocatalyst can greatly accelerate the catalytic conversion of polysulfides, thereby inhibiting the shuttling effect and utilization rate of polysulfides, and finally obtaining a lithium-sulfur battery with high capacity, high rate and long cycle. CN111682214A discloses a metal atom-non-metal atom co-doped graphene catalyst, which is based on graphene, and the graphene main body is doped with metal atoms and non-metal atoms, and the metal atoms and non-metal atoms are coordinated and distributed in the graphene lattice; the metal atoms are single atoms or polyatoms. The catalyst can catalyze the conversion between sulfur-containing species, limit the shuttling of polysulfides, and maximize its catalytic performance without affecting the battery energy density. Although single-atom catalysts are used in the positive electrode of lithium-sulfur batteries, single-atom catalysts are mostly used to modify sulfur carriers, and cannot effectively achieve high-proportion adsorption of polysulfides to inhibit their dissolution and shuttling. For this reason, it is necessary to provide a new lithium-sulfur battery positive electrode structure, which suppresses the shuttling effect of polysulfides while maintaining the positive electrode energy density, and realizes effective catalysis and bidirectional conversion of sulfides in lithium-sulfur batteries, thereby improving the performance of lithium-sulfur batteries. Summary of the invention

[0005] In order to solve the defects in the prior art, the present invention provides a lithium-sulfur battery positive electrode and a preparation method thereof, specifically, an active sulfur-graphene composite material is introduced into the positive electrode active layer of the lithium-sulfur battery as the positive electrode active material, the active sulfur is a sublimated sulfur particle with a single cerium atom loaded on the surface, the introduction of the cerium single atom catalyst can improve the conductivity of the sulfur particles, and at the same time, the cerium single atom layer itself can effectively adsorb and convert polysulfides on the surface of the sulfur positive electrode, inhibiting its shuttle effect, and can effectively inhibit the shuttling of polysulfides in combination with the physical barrier of graphene; cerium has a high selective adsorption of long-chain polysulfides, reduces the redox reaction energy barrier of polysulfides, improves the utilization rate of sulfur, reduces the loss of active substances, and improves the coulombic efficiency, cycle stability and charge and discharge efficiency of the battery.

[0006] To achieve the above-mentioned object of the present invention, the present invention provides a positive electrode for a lithium-sulfur battery, comprising a current collector and a positive electrode active layer located on the current collector, wherein the positive electrode active layer comprises an active sulfur-graphene composite material, a conductive agent and polyvinylidene fluoride; the active sulfur is a sublimated sulfur particle with a single cerium atom loaded on the surface. Cerium (Ce), as a rare earth element, has a rich 4f electronic structure. When a single atomic layer of cerium is coated on the surface of sulfur particles, the 4f electrons of cerium can strongly interact with the p orbital of sulfur, change the electronic structure of sulfur, and increase the concentration of free electrons. This makes it easier for sulfur to participate in electrochemical reactions, thereby improving the utilization rate of sulfur; the cerium single atomic layer has excellent catalytic activity, can significantly reduce the redox reaction energy barrier of polysulfide, accelerate the conversion of long-chain polysulfide to short-chain polysulfide, and reduce the accumulation of intermediate products; the cerium single atomic layer can form a strong chemical bond with the sulfur atoms in the polysulfide, effectively adsorb and fix the polysulfide, and reduce the generation of soluble polysulfide; the sublimated sulfur particles with cerium single atoms on the surface are composited with graphene to build an efficient conductive network, ensuring the rapid transmission of electrons in the entire electrode, which not only improves the conductivity of sulfur, but also enhances the conductivity of the entire positive electrode and improves the rate performance of the battery. Compared with the conventional rare earth single atom catalyst set on the sulfur carrier, the scheme of the present invention can act directly on the sulfur particles, the overall battery performance is better, and the effective utilization rate of sulfur is higher.

[0007] Furthermore, the current collector is aluminum foil, and the mass fraction of active sulfur in the active sulfur-graphene composite material is 75-90wt%, which can ensure that the sulfur content in the positive electrode is sufficiently high, and can achieve uniform dispersion of sulfur, avoid agglomeration of sulfur particles, thereby making full use of its high specific capacity and improving the overall energy density of the battery.

[0008] Furthermore, the mass fraction of the active sulfur-graphene composite material in the positive electrode active layer is 70-90wt%, the mass fraction of the conductive agent is 5-20wt%, and the mass fraction of polyvinylidene fluoride is 2-10wt%. In the positive electrode with a high sulfur content, an appropriate amount of binder can ensure good bonding between the electrode materials and prevent the electrode from falling off or stratifying during charging and discharging. At the same time, the amount of binder should not be too high to avoid affecting the energy density and electrochemical performance of the battery.

[0009] Furthermore, the conductive agent is any one of acetylene black, superconducting carbon black, conductive graphite, carbon nanotubes, and carbon fibers.

[0010] Furthermore, the mass ratio of the cerium atom in the active sulfur is 2wt% to 8wt%, and the particle size of the sublimated sulfur particles is 10nm to 500nm.

[0011] Furthermore, the active sulfur is prepared by the following method: placing high-purity sulfur powder in a vacuum sublimation furnace, under nitrogen protection, controlling the temperature to 400-500° C., the sublimation time to 2-5 hours, and collecting sublimated sulfur particles; preparing a 0.05M cerium nitrate aqueous solution, adding 80-350g of sublimated sulfur particles thereto, stirring until uniformly dispersed, then adding 0.2mol of sodium borohydride thereto, stirring until uniformly dispersed, transferring the mixed solution to a stainless steel autoclave, reacting at 100-150° C. for 3h, cooling to room temperature, washing, filtering, and putting the filter residue into an oven to fully dry and then grinding it into powder to obtain the active sulfur. In addition, the introduction of a single atomic layer of cerium on active sulfur can also be done by the ALD method. ALD is a high-precision vapor deposition technology that can deposit single atomic layer materials layer by layer at the nanoscale. By alternately introducing cerium precursors such as cerium chloride or cerium nitrate and reducing agents such as trimethylaluminum TMA, single cerium atoms can be uniformly deposited on the surface of sulfur particles. After each introduction, a short purge is performed to remove unreacted gases. Before the reaction, sulfur particles can be placed in the ALD reaction chamber for high-temperature annealing or surface modification pretreatment to increase the active sites on the sulfur surface. This method can accurately control the loading amount of single cerium atoms and can accurately regulate the distribution and coordination environment of single cerium atoms at the nanoscale. However, the equipment is complex, the cost is high, and the deposition rate is slow.

[0012] Furthermore, the preparation method of the active sulfur-graphene composite material is as follows: weigh active sulfur and graphene respectively, mix the two and stir at high speed for 2 to 5 hours, heat to 130° C. in a nitrogen atmosphere and keep warm for 10 to 20 hours to obtain the active sulfur-graphene composite material.

[0013] Furthermore, the lithium-sulfur battery positive electrode preparation method is as follows: 1) weighing an active sulfur-graphene composite material, a conductive agent and polyvinylidene fluoride in proportion; 2) using N-methylpyrrolidone as a solvent to prepare a slurry of the active sulfur-graphene composite material, the conductive agent and polyvinylidene fluoride, coating the slurry on an aluminum foil, and drying the slurry to obtain a positive electrode active layer with a thickness of 300-1000 μm.

[0014] Another object of the present invention is to provide a method for preparing a positive electrode of a lithium-sulfur battery, comprising the following steps:

[0015] 1. Preparation of active sulfur-graphene composite materials: placing high-purity sulfur powder in a vacuum sublimation furnace, under nitrogen protection, controlling the temperature to 400-500°C, sublimation time to 2-5 hours, collecting sublimated sulfur particles; preparing a 0.05M cerium nitrate aqueous solution, adding 80-350g of sublimated sulfur particles thereto, stirring until uniformly dispersed, then adding 0.2mol of sodium borohydride thereto, stirring thoroughly until uniformly dispersed, transferring the mixture to a stainless steel autoclave, and heating at 100- The mixture was reacted at 150° C. for 3 hours, cooled to room temperature, washed, filtered, and the filter residue was placed in an oven for full drying and then ground into powder to obtain active sulfur particles with an average particle size of 10 nm to 500 nm and a cerium single atom content of 2 wt% to 8 wt%; active sulfur particles and graphene were weighed according to an active sulfur mass fraction of 75 to 90 wt%, the two were mixed and stirred at high speed for 2 to 5 hours, and heated to 130° C. in a nitrogen atmosphere and kept warm for 10 to 20 hours to obtain an active sulfur-graphene composite material;

[0016] 2. Preparation of positive electrode active layer: Weigh active sulfur-graphene composite material, conductive agent and polyvinylidene fluoride in a mass ratio of 70-90:5-20:2-10; Use N-methylpyrrolidone as solvent, add active sulfur-graphene composite material, conductive agent and polyvinylidene fluoride into the solvent in sequence to prepare slurry, coat the slurry on aluminum foil, and dry to obtain.

[0017] The present invention also provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises a current collector and a positive electrode active layer located on the current collector, wherein the positive electrode active layer comprises an active sulfur-graphene composite material, a conductive agent and polyvinylidene fluoride; the active sulfur is sublimated sulfur particles with single cerium atoms loaded on the surface, and the thickness of the positive electrode active layer is 300-1000 μm.

[0018] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0019] 1. The lithium-sulfur battery prepared by the present invention can effectively inhibit the shuttling effect of polysulfide in the lithium-sulfur battery. The cerium atom has a rich 4f electronic structure and can strongly interact with the sulfur atoms in the polysulfide. The cerium single-atom catalyst can form a strong chemical bond with the polysulfide to effectively adsorb and fix the polysulfide. At the same time, the cerium single-atom catalyst has a high selective adsorption capacity for long-chain polysulfides, can preferentially adsorb these polysulfides with strong solubility, and promote their conversion into short-chain polysulfides, which helps to improve the utilization rate of sulfur and reduce the loss of active substances. The cerium single-atom catalyst can also significantly reduce the redox reaction energy barrier of polysulfide, especially for long-chain polysulfide, the single-atom catalyst can accelerate its conversion to short-chain polysulfide, reduce the accumulation of intermediate products, so that the polysulfide is adsorbed near the positive electrode sulfur, inhibits its diffusion, and accelerates its redox reaction, and also improves the coulombic efficiency and cycle stability of the battery as well as the charge and discharge efficiency of the battery.

[0020] 2. In the positive electrode active layer of the lithium-sulfur battery prepared by the present invention, sublimated sulfur particles with single cerium atoms loaded on the surface are used as active sulfur. The single cerium atom catalyst can promote electron transfer by regulating the electronic structure of sulfur, introduce a conductive path, enhance the conductivity of sulfur, promote the rapid transmission of electrons in the entire electrode, and improve the rate performance of the battery; at the same time, the 4f orbital electrons of the single cerium atom catalyst have strong localization characteristics, can form a stable coordination structure on the sulfur surface, can form a stable chemical bond with sulfur, limit the volume expansion of sulfur during the charge and discharge process, maintain the structural integrity of the sulfur positive electrode, and reduce the electrode pulverization and shedding caused by volume change, thereby extending the cycle life of the battery.

[0021] 3. The positive electrode of the present invention adopts a composite material of active sulfur and graphene. The active sulfur is a sublimated sulfur particle with a single cerium atom loaded on the surface. Graphene can form an effective physical barrier in the electrolyte to prevent the diffusion of polysulfides. The single cerium atom on the surface of the sulfur particle can adsorb and fix polysulfides. The combination of the two can more effectively inhibit the shuttle effect of polysulfides; the conductive agent in the graphene and the positive electrode can build an efficient conductive network to ensure the rapid transmission of electrons in the entire electrode. This synergistic effect not only improves the conductivity of sulfur, but also enhances the mechanical strength of the positive electrode and reduces the problems caused by volume expansion. DETAILED DESCRIPTION

[0022] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0023] It should be noted that the reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0024] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.

[0025] The performance test of the lithium-sulfur battery in the present invention is conducted by assembling a 2032 lithium-sulfur button battery, specifically: the prepared positive electrode is cut into a small disc with a diameter of 12 mm, and then a commercial lithium sheet of the same size is used as the negative electrode, the electrolyte is a 1,3-dioxolane / ethylene glycol dimethyl ether (DOL / DME, volume ratio of 1:1) solution containing 1 mol lithium bistrifluoromethylsulfonyl imide (LiTFSI) and 0.1 mol / L lithium nitrate (LiNO3), and the diaphragm is Celgard 2400, which is assembled into a 2032 button battery. The specific assembly method is: place the positive electrode in the positive electrode shell, add 100 mL of electrolyte, put in the diaphragm, then place the negative electrode on the diaphragm, add a gasket shrapnel and a negative electrode shell on the negative electrode in turn, and finally press the positive electrode shell and the negative electrode shell together under a pressure of 50 MPa to obtain a 2032 button battery.

[0026] Example 1

[0027] A lithium-sulfur battery positive electrode, the preparation method comprises the following steps:

[0028] 1. Preparation of active sulfur-graphene composite materials: placing high-purity sulfur powder in a vacuum sublimation furnace, under nitrogen protection, controlling the temperature to 400° C., sublimation time to 2 hours, and collecting sublimated sulfur particles; preparing a 0.05M cerium nitrate aqueous solution, adding 80g of sublimated sulfur particles thereto, stirring until uniformly dispersed, then adding 0.2mol of sodium borohydride thereto, stirring fully until uniformly dispersed, transferring the mixed solution to a stainless steel autoclave, reacting at 100° C. for 3h, cooling to room temperature, washing, filtering, placing the filter residue in an oven to fully dry, and then grinding it into powder to obtain active sulfur particles with an average particle size of 10nm~100nm; weighing active sulfur particles and graphene according to the active sulfur mass fraction of 75wt%, mixing the two and stirring at high speed for 2h, heating to 130° C. in a nitrogen atmosphere and keeping the temperature for 10 hours, and obtaining an active sulfur-graphene composite material.

[0029] 2. Preparation of positive electrode active layer: Weigh active sulfur-graphene composite material, conductive agent acetylene black and polyvinylidene fluoride in a mass ratio of 70:20:10; Use N-methylpyrrolidone as solvent to add active sulfur-graphene composite material, acetylene black and polyvinylidene fluoride into the solvent in sequence to prepare slurry, coat the slurry on aluminum foil, and dry. The thickness of the positive electrode active layer is 300 μm.

[0030] The active sulfur was tested and it was found that the cerium single atom content in the active sulfur particles was 8wt%. The lithium-sulfur battery using this positive electrode was tested and the first cycle discharge capacity was 1320mAh g at a rate of 1C. -1 After 800 cycles, the capacity retention rate was 98.1%; at a rate of 2C, the first cycle discharge capacity was 1148 mAh g -1 , the capacity retention rate is 91% after 1000 cycles.

[0031] Example 2

[0032] A lithium-sulfur battery positive electrode, the preparation method comprises the following steps:

[0033] 1. Preparation of active sulfur-graphene composite materials: placing high-purity sulfur powder in a vacuum sublimation furnace, under nitrogen protection, controlling the temperature to 500° C., sublimation time to 5 hours, and collecting sublimated sulfur particles; preparing a 0.05M cerium nitrate aqueous solution, adding 350g of sublimated sulfur particles thereto, stirring until uniformly dispersed, then adding 0.2mol of sodium borohydride thereto, stirring fully until uniformly dispersed, transferring the mixed solution to a stainless steel autoclave, reacting at 150° C. for 3h, cooling to room temperature, washing, filtering, placing the filter residue in an oven to fully dry and then grinding it into powder to obtain active sulfur particles with an average particle size of 100nm~500nm; weighing active sulfur particles and graphene according to the active sulfur mass fraction of 90wt%, mixing the two and stirring at high speed for 5h, heating to 130° C. in a nitrogen atmosphere and keeping the temperature for 20 hours, and obtaining an active sulfur-graphene composite material.

[0034] 2. Prepare the positive electrode active layer: weigh the active sulfur-graphene composite material, the conductive agent superconducting carbon black and polyvinylidene fluoride in a mass ratio of 90:5:5; use N-methylpyrrolidone as a solvent, add the active sulfur-graphene composite material, the conductive agent superconducting carbon black and polyvinylidene fluoride into the solvent in sequence to form a slurry, coat the slurry on an aluminum foil, and dry it, wherein the thickness of the positive electrode active layer is 1000 μm.

[0035] The active sulfur was tested and it was found that the cerium single atom content in the active sulfur particles was 2wt%. The lithium-sulfur battery using this positive electrode was tested and the first cycle discharge capacity was 1560mAh g at a rate of 1C. -1After 800 cycles, the capacity retention rate was 95.7%; at a rate of 2C, the first cycle discharge capacity was 1219 mAh g -1 , the capacity retention rate after 1000 cycles is 90.5%.

[0036] Example 3

[0037] A lithium-sulfur battery positive electrode, the preparation method comprises the following steps:

[0038] 1. Preparation of active sulfur-graphene composite materials: placing high-purity sulfur powder in a vacuum sublimation furnace, under nitrogen protection, controlling the temperature to 450° C., sublimation time to 4 hours, and collecting sublimated sulfur particles; preparing a 0.05M cerium nitrate aqueous solution, adding 150g of sublimated sulfur particles thereto, stirring until uniformly dispersed, then adding 0.2mol of sodium borohydride thereto, stirring fully until uniformly dispersed, transferring the mixed solution to a stainless steel autoclave, reacting at 130° C. for 3h, cooling to room temperature, washing, filtering, placing the filter residue in an oven to fully dry, and then grinding it into powder to obtain active sulfur particles with an average particle size of 50nm~200nm; weighing active sulfur particles and graphene according to the active sulfur mass fraction of 80wt%, mixing the two and stirring at high speed for 5h, heating to 130° C. in a nitrogen atmosphere and keeping the temperature for 15 hours, and obtaining an active sulfur-graphene composite material.

[0039] 2. Prepare the positive electrode active layer: weigh the active sulfur-graphene composite material, the conductive carbon nanotube and polyvinylidene fluoride in a mass ratio of 88:10:2; use N-methylpyrrolidone as a solvent, add the active sulfur-graphene composite material, the conductive carbon nanotube and polyvinylidene fluoride into the solvent in sequence to prepare a slurry, coat the slurry on an aluminum foil, and dry it, wherein the thickness of the positive electrode active layer is 800 μm.

[0040] The active sulfur was tested and it was found that the cerium single atom content in the active sulfur particles was 5.3wt%. The lithium-sulfur battery using this positive electrode was tested and the first cycle discharge capacity was 1398mAh g at a rate of 1C. -1 After 800 cycles, the capacity retention rate was 97.4%; at a rate of 2C, the first cycle discharge capacity was 1182 mAh g -1 , the capacity retention rate is 92.3% after 1000 cycles.

[0041] Example 4

[0042] A lithium-sulfur battery positive electrode, the preparation method comprises the following steps:

[0043] 1. Preparation of active sulfur-graphene composite materials: placing high-purity sulfur powder in a vacuum sublimation furnace, under nitrogen protection, controlling the temperature to 480°C, the sublimation time to 3 hours, and collecting sublimated sulfur particles; preparing a 0.05M cerium nitrate aqueous solution, adding 200g of sublimated sulfur particles thereto, stirring until uniformly dispersed, then adding 0.2mol of sodium borohydride thereto, stirring fully until uniformly dispersed, transferring the mixed solution to a stainless steel autoclave, reacting at 110°C for 3h, cooling to room temperature, washing, filtering, placing the filter residue in an oven to fully dry and then grinding it into powder to obtain active sulfur particles with an average particle size of 70nm~300nm; weighing active sulfur particles and graphene according to the active sulfur mass fraction of 85 wt%, mixing the two and stirring at high speed for 4h, heating to 130°C in a nitrogen atmosphere and keeping warm for 18 hours, and obtaining an active sulfur-graphene composite material.

[0044] 2. Preparation of positive electrode active layer: Weigh active sulfur-graphene composite material, conductive carbon fiber and polyvinylidene fluoride in a mass ratio of 80:15:5; Use N-methylpyrrolidone as solvent to add active sulfur-graphene composite material, conductive carbon fiber and polyvinylidene fluoride into the solvent in sequence to prepare slurry, coat the slurry on aluminum foil, and dry to obtain, wherein the thickness of the positive electrode active layer is 600 μm.

[0045] The active sulfur was tested and it was found that the cerium single atom content in the active sulfur particles was 4.1wt%. The lithium-sulfur battery using this positive electrode was tested and the first cycle discharge capacity was 1355mAh g at a rate of 1C. -1 After 800 cycles, the capacity retention rate is 93.8%; the first cycle discharge capacity at a rate of 2C is 1050mAh g -1 , the capacity retention rate after 1000 cycles is 90.6%.

[0046] Comparative Example 1

[0047] A lithium-sulfur battery positive electrode, the preparation method comprises the following steps:

[0048] 1. Preparation of active sulfur material: placing high-purity sulfur powder in a vacuum sublimation furnace, under nitrogen protection, controlling the temperature to 480°C, sublimation time to 3 hours, collecting sublimated sulfur particles, grinding to obtain active sulfur particles with an average particle size of 100nm~200nm; weighing active sulfur particles and graphene according to the active sulfur mass fraction of 85wt%, mixing the two and stirring at high speed for 4h, heating to 130°C in a nitrogen atmosphere and keeping warm for 18 hours, and obtaining an active sulfur-graphene composite material.

[0049] 2. Preparation of positive electrode active layer: Weigh active sulfur-graphene composite material, conductive carbon fiber and polyvinylidene fluoride in a mass ratio of 80:15:5; Use N-methylpyrrolidone as solvent to add active sulfur-graphene composite material, conductive carbon fiber and polyvinylidene fluoride into the solvent in sequence to prepare slurry, coat the slurry on aluminum foil, and dry to obtain, wherein the thickness of the positive electrode active layer is 600 μm.

[0050] The lithium-sulfur battery using this positive electrode was tested and the first cycle discharge capacity was 1047 mAh g at a rate of 1C. -1 After 800 cycles, the capacity retention rate was 64.6%; at a rate of 2C, the first cycle discharge capacity was 828 mAh g -1 , the capacity retention rate is 49.3% after 1000 cycles.

[0051] Comparative Example 2

[0052] A lithium-sulfur battery positive electrode, the preparation method comprises the following steps:

[0053] 1. Preparation of active sulfur-graphene composite materials: placing high-purity sulfur powder in a vacuum sublimation furnace, under nitrogen protection, controlling the temperature to 480° C., sublimation time to 3 hours, and collecting sublimated sulfur particles; preparing a 0.05M cerium nitrate aqueous solution, adding 35g of graphene thereto, stirring until uniformly dispersed, then adding 0.2mol of sodium borohydride thereto, stirring fully until uniformly dispersed, transferring the mixed solution to a stainless steel autoclave, reacting at 110° C. for 3h, cooling to room temperature, washing, filtering, placing the filter residue in an oven to be fully dried, and then grinding it into powder; weighing sublimated sulfur particles and dried and ground graphene powder according to the active sulfur mass fraction of 85wt%, mixing the two, stirring at high speed for 4h, heating to 130° C. in a nitrogen atmosphere, and keeping the temperature for 18h, to obtain an active sulfur-graphene composite material.

[0054] 2. Preparation of positive electrode active layer: Weigh active sulfur-graphene composite material, conductive carbon fiber and polyvinylidene fluoride in a mass ratio of 80:15:5; Use N-methylpyrrolidone as solvent to add active sulfur-graphene composite material, conductive carbon fiber and polyvinylidene fluoride into the solvent in sequence to prepare slurry, coat the slurry on aluminum foil, and dry to obtain, wherein the thickness of the positive electrode active layer is 600 μm.

[0055] The active sulfur-graphene composite material was tested and it was found that the cerium single atom content in the active sulfur particles in the graphene was 10.3wt%. The lithium-sulfur battery using this positive electrode was tested and the first cycle discharge capacity was 1209mAh g at a rate of 1C. -1 After 800 cycles, the capacity retention rate was 83.4%; at a rate of 2C, the first cycle discharge capacity was 998 mAh g -1, the capacity retention rate after 1000 cycles is 69.1%.

[0056] Comparative Example 3

[0057] A lithium-sulfur battery positive electrode, the preparation method comprises the following steps:

[0058] 1. Preparation of active sulfur material: placing high-purity sulfur powder in a vacuum sublimation furnace, under nitrogen protection, controlling the temperature to 480°C, the sublimation time to 3 hours, and collecting sublimated sulfur particles; preparing a 0.05M cerium nitrate aqueous solution, adding 200g of sublimated sulfur particles thereto, stirring until uniformly dispersed, then adding 0.2mol of sodium borohydride thereto, stirring fully until uniformly dispersed, transferring the mixed solution to a stainless steel autoclave, reacting at 110°C for 3h, cooling to room temperature, washing, filtering, placing the filter residue in an oven to fully dry, and then grinding it into powder to obtain active sulfur particles with an average particle size of 70nm~300nm.

[0059] 2. Prepare a positive electrode active layer: weigh active sulfur, conductive carbon fiber and polyvinylidene fluoride in a mass ratio of 70:25:5; use N-methylpyrrolidone as a solvent, add active sulfur, conductive carbon fiber and polyvinylidene fluoride into the solvent in sequence to form a slurry, coat the slurry on an aluminum foil, and dry it, wherein the thickness of the positive electrode active layer is 600 μm.

[0060] The active sulfur was tested and it was found that the cerium single atom content in the active sulfur particles was 4.1wt%. The lithium-sulfur battery using this positive electrode was tested and the first cycle discharge capacity was 1447mAh g at a rate of 1C. -1 After 800 cycles, the capacity retention rate was 71.2%; at a rate of 2C, the first cycle discharge capacity was 1105 mAh g -1 , the capacity retention rate after 1000 cycles is 55.8%.

[0061] Comparative Example 4

[0062] A lithium-sulfur battery positive electrode, the preparation method comprises the following steps:

[0063] 1. Preparation of active sulfur-graphene composite materials: placing high-purity sulfur powder in a vacuum sublimation furnace, under nitrogen protection, controlling the temperature to 480° C., sublimation time to 3 hours, and collecting sublimated sulfur particles; preparing a 0.2M cerium nitrate aqueous solution, adding 200g of sublimated sulfur particles thereto, stirring until uniformly dispersed, then adding 0.6mol of sodium borohydride thereto, stirring fully until uniformly dispersed, transferring the mixed solution to a stainless steel autoclave, reacting at 170° C. for 10 hours, cooling to room temperature, washing, filtering, placing the filter residue in an oven to fully dry and then grinding it into powder to obtain active sulfur particles with an average particle size of 30nm~800nm; weighing active sulfur particles and graphene according to the active sulfur mass fraction of 65wt%, mixing the two and stirring at high speed for 4h, heating to 170° C. in a nitrogen atmosphere and keeping the temperature for 18 hours, and obtaining an active sulfur-graphene composite material.

[0064] 2. Preparation of positive electrode active layer: Weigh active sulfur-graphene composite material, conductive carbon fiber and polyvinylidene fluoride in a mass ratio of 65:25:10; Use N-methylpyrrolidone as solvent to add active sulfur-graphene composite material, conductive carbon fiber and polyvinylidene fluoride into the solvent in sequence to prepare slurry, coat the slurry on aluminum foil, and dry to obtain, wherein the thickness of the positive electrode active layer is 600 μm.

[0065] The active sulfur was tested and it was found that the cerium single atom content in the active sulfur particles was 11.3wt%. The lithium-sulfur battery using this positive electrode was tested and the first cycle discharge capacity was 1317mAh g at a rate of 1C. -1 After 800 cycles, the capacity retention rate was 78.3%; at a rate of 2C, the first cycle discharge capacity was 972 mAh g -1 , the capacity retention rate is 61.5% after 1000 cycles.

[0066] It can be seen from the above test data that the lithium-sulfur battery prepared based on the method of the present invention has a high discharge capacity and good cycle stability. From the first cycle discharge capacity at 2C rate and the discharge capacity after 1000 cycles of the electrode, it can be seen that the lithium-sulfur battery prepared by the present invention has a good discharge specific energy, and the battery cycle stability is good after long-term discharge, indicating that the lithium-sulfur battery in the embodiment of the present invention can effectively inhibit the shuttle of polysulfide, the utilization rate of sulfur is high, and the cycle life of the battery is good. After analysis, the above performance is mainly due to the strong chemical bonding between the cerium single atom and the polysulfide, the high selective adsorption of long-chain polysulfide, the reduction of the redox reaction energy barrier of the polysulfide, and the reduction of the loss of active substances. At the same time, the above treatment enhances the conductivity of sulfur to a certain extent, promotes the rapid transmission of electrons in the entire electrode, and improves the rate performance of the battery.

[0067] The above is a detailed introduction to a lithium-sulfur battery positive electrode and its preparation method. The above content is a further detailed description of the present invention in combination with a specific preferred embodiment, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.

Claims

1. A positive electrode for a lithium-sulfur battery, comprising a current collector and a positive electrode active layer on the current collector, characterized in that: The positive electrode active layer comprises an active sulfur-graphene composite material, a conductive agent and polyvinylidene fluoride; the active sulfur is sublimated sulfur particles with single cerium atoms loaded on the surface, the mass fraction of active sulfur in the active sulfur-graphene composite material is 75-90wt%, the mass ratio of single cerium atoms in the active sulfur is 2wt%-8wt%, and the particle size of the sublimated sulfur particles is 10nm-500nm.

2. The lithium-sulfur battery positive electrode according to claim 1, characterized in that: The current collector is aluminum foil.

3. The lithium-sulfur battery positive electrode according to claim 1, characterized in that: The mass fraction of the active sulfur-graphene composite material in the positive electrode active layer is 70-90wt%, the mass fraction of the conductive agent is 5-20wt%, and the mass fraction of polyvinylidene fluoride is 2-10wt%.

4. The lithium-sulfur battery positive electrode according to claim 1, characterized in that: The conductive agent is any one of acetylene black, superconducting carbon black, conductive graphite, carbon nanotubes, and carbon fibers.

5. The lithium-sulfur battery positive electrode according to claim 1, characterized in that: The active sulfur is prepared by the following method: placing high-purity sulfur powder in a vacuum sublimation furnace, controlling the temperature to 400-500° C. under nitrogen protection, sublimation time to 2-5 hours, and collecting sublimated sulfur particles; preparing a 0.05M cerium nitrate aqueous solution, adding 80-350g of sublimated sulfur particles thereto, stirring until uniform dispersion, then adding 0.2mol of sodium borohydride thereto, stirring fully until uniform dispersion, transferring the mixed solution to a stainless steel autoclave, reacting at 100-150° C. for 3h, cooling to room temperature, washing, filtering, putting the filter residue into an oven for full drying, and then grinding it into powder to obtain the active sulfur.

6. The lithium-sulfur battery positive electrode according to claim 1, characterized in that: The preparation method of the active sulfur-graphene composite material is as follows: active sulfur and graphene are weighed respectively, the two are mixed and stirred at high speed for 2-5 hours, and heated to 130° C. in a nitrogen atmosphere and kept warm for 10-20 hours to obtain the active sulfur-graphene composite material.

7. The lithium-sulfur battery positive electrode according to claim 1, characterized in that: The lithium-sulfur battery positive electrode preparation method is as follows: 1) weighing an active sulfur-graphene composite material, a conductive agent and polyvinylidene fluoride according to a proportion; 2) Using N-methylpyrrolidone as a solvent, the active sulfur-graphene composite material, the conductive agent and polyvinylidene fluoride are made into a slurry, the slurry is coated on an aluminum foil, and dried to obtain a positive electrode active layer with a thickness of 300-1000 μm.

8. A method for preparing a lithium-sulfur battery positive electrode according to any one of claims 1 to 7, characterized in that: The steps include:

1. Preparation of active sulfur-graphene composite materials: placing high-purity sulfur powder in a vacuum sublimation furnace, under nitrogen protection, controlling the temperature to 400-500°C, sublimation time to 2-5 hours, collecting sublimated sulfur particles; preparing a 0.05M cerium nitrate aqueous solution, adding 80-350g of sublimated sulfur particles thereto, stirring until uniformly dispersed, then adding 0.2mol of sodium borohydride thereto, stirring thoroughly until uniformly dispersed, transferring the mixture to a stainless steel autoclave, and heating at 100- The mixture was reacted at 150° C. for 3 hours, cooled to room temperature, washed, filtered, and the filter residue was placed in an oven for full drying and then ground into powder to obtain active sulfur particles with an average particle size of 10 nm to 500 nm and a cerium single atom content of 2 wt% to 8 wt%; active sulfur particles and graphene were weighed according to an active sulfur mass fraction of 75 to 90 wt%, the two were mixed and stirred at high speed for 2 to 5 hours, and heated to 130° C. in a nitrogen atmosphere and kept warm for 10 to 20 hours to obtain an active sulfur-graphene composite material; 2. Preparation of positive electrode active layer: Weigh active sulfur-graphene composite material, conductive agent and polyvinylidene fluoride in a mass ratio of 70-90:5-20:2-10; Use N-methylpyrrolidone as solvent, add active sulfur-graphene composite material, conductive agent and polyvinylidene fluoride into the solvent in sequence to prepare slurry, coat the slurry on aluminum foil, and dry to obtain.

9. A lithium-sulfur battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode is the battery positive electrode according to any one of claims 1 to 7, and the thickness of the positive electrode active layer is 300 to 1000 μm.

Citation Information

Patent Citations

  • Metal monoatom-doped carbon nanomaterial catalytic carrier, and preparation method and application thereof

    CN109248712A

  • Sulfur-carrying material and positive electrode material of lithium-sulfur battery

    CN111403702A

  • Metal atom-nonmetal atom co-doped graphene catalyst, preparation method thereof, positive electrode material and lithium-sulfur battery

    CN111682214A

  • Monatomic electrocatalyst and preparation method and application thereof

    CN113731392A

  • Lithium battery positive electrode based on graphene-sulfur composite material and preparation method thereof

    CN109461910A